Lone wolf - Hurwitz, Gregg (New York : Minotaur Books, 2024)
Orphan X helps a little girl find her missing dog and finds himself battered between feuding AI technocrat billionaires and a female assassin called the Wolf in the ninth novel of the series following.
Keywords: Smoak, Evan -- (Fictitious character) -- Fiction; Assassins -- Fiction; Artificial intelligence -- Fiction; Billionaires -- Fiction; Good and evil -- Fiction; Thrillers (Fiction)